Penyusunan Instrumen Penilaian Kognitif Pada Pembelajaran Pendidikan Agama Islam - Risnawati Risnawati; Miftahir Rizqa; Anisa Fitri; Ilham Muhammad; Okfrida Hidayati; Radhiatul Husni (Institut Agama Islam Sumatera Barat, 2023)
This research aims to explain how to compile knowledge assessment instruments (cognitive), including tests consisting of objective tests, essay tests, matchmaking tests, true false tests and also how to score in each type of cognitive tests. The method used in this paper is the library research method. The literature method is a research method carried out by obtaining data from various sources, including books in libraries, magazines or documents related to the topic discussed. The results of the study concluded that the cognitive realm is a process of knowledge that is more based on its development from perception, introspection or memory of students. According to Bloom, cognitive learning objectives are developed at six levels: knowledge, comprehension, application, analysis, synthesis and evaluation. To determine the ability of students according to the levels in cognitive learning objectives, a measuring tool is needed, namely tests. Tests in this cognitive realm include objective tests, description tests, matchmaking tests and true false tests.